Sociodemographic inequalities in mortality from drowning in the Baltic countries and Finland in 2000-2015: a register-based study - Andrew Stickley; Aleksei Baburin; Domantas Jasilionis; Juris Krumins; Pekka Martikainen; Naoki Kondo; Jae Il Shin; Yosuke Inoue; Mall Leinsalu (BMC, 2023)
Abstract Background Drowning is an important public health problem. Some evidence suggests that the risk of drowning is not distributed evenly across the general population. However, there has been comparatively little research on inequalities in drowning mortality. To address this deficit, this study examined trends and sociodemographic inequalities in mortality from unintentional drowning in the Baltic countries and Finland in 2000-2015. Methods Data for Estonia, Latvia and Lithuania came from longitudinal mortality follow-up studies of population censuses in 2000/2001 and 2011, while corresponding data for Finland were obtained from the longitudinal register-based population data file of Statistics Finland. Deaths from drowning (ICD-10 codes W65-W74) were obtained from national mortality registries. Information was also obtained on socioeconomic status (educational level) and urban-rural residence. Age-standardised mortality rates (ASMRs) per 100 000 person years and mortality rate ratios were calculated for adults aged 30-74 years old. Poisson regression analysis was performed to assess the independent effects of sex, urban-rural residence and education on drowning mortality. Results Drowning ASMRs were significantly higher in the Baltic countries than in Finland but declined by nearly 30% in all countries across the study period. There were large inequalities by sex, urban-rural residence and educational level in all countries during 2000-2015. Men, rural residents and low educated individuals had substantially higher drowning ASMRs compared to their counterparts. Absolute and relative inequalities were significantly larger in the Baltic countries than in Finland. Absolute inequalities in drowning mortality declined in all countries across the study period except between urban and rural residents in Finland. Changes in relative inequalities were more variable during 2000-2015. Conclusion Despite a sharp reduction in deaths from drowning in the Baltic countries and Finland in 2000-2015, drowning mortality was still high in these countries at the end of the study period with a substantially larger risk of death seen among men, rural residents and low educated individuals. A concerted effort to prevent drowning mortality among those most at risk may reduce drownings considerably in the general population.